The Images of Heroism in The Poetry of Ka’ab bin Malik and Mustofa Bisri: A Comparative Study - Ibnu Hudzaifah Hamka; Nursafira Lubis Safian (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2022)
Ka'ab bin Malik is considered one of the greatest poets of the Messenger of God, and witnessed various battles with the Messenger of God On the other hand, Mustafa Bisri is an Indonesian writer who deserved recognition for his activities in the field of Indonesian literature. This study deals with a comparison of Arabic poetry and Indonesian poetry between Kaab bin Malik and Mustafa Bisri. The study aims to reveal aspect of agreements and differences in potraying heroism between them. This study follows three approaches: the qualitative approach by describing the lives of the two poets and the analytical approach by studying the concept and tracing poems about the heroism between Ka’ab bin Malik and Mustafa Bisri. And the comparative approach to present a comparison of the images of heroism between the two writers. For the results of the study: The two poets agreed in the heroism that they are people of courage, although they expressed heroism in ways and methods that differ from each other, but the scope of courage is connected to the listeners and readers. In addition, the opinions of the two poets differed about the depiction of heroism in their poems. The researcher presents the heroism of Ka’ab bin Malik with three images: leadership, martyrdom, and jihad. Mustafa portrayed heroism in his poetry, five images: determination, fragrant flowers, patriotism, courage, and the best generation.